2020
DOI: 10.1038/s41598-020-72909-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of anodal tDCS intensity threshold for reversal of corticospinal excitability: an investigation for induction of counter-regulatory mechanisms

Abstract: Transcranial direct current stimulation is applied to modulate activity, and excitability of the brain. Basically, LTP-like plasticity is induced when anodal tDCS (a-tDCS) is applied over the primary motor cortex. However, it has been shown that specific parameters of a-tDCS can induce a plasticity reversal. We aimed to systematically assess the intensity threshold for reversal of the direction of plasticity induced by a-tDCS, monitored by corticospinal excitability (CSE), and explored mechanisms regulating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 46 publications
0
23
0
Order By: Relevance
“…In contrast, event-related TDCS may selectively modulate only those circuits and task-related synapses that are contemporaneously active and undergoing concurrent plasticity [16,41]. As such, er-TDCS could prove beneficial when long experimental or rehabilitative protocols are required, as recent research suggests that long continuous bouts of TDCS may cause the resultant modulatory effects to diminish and even reverse over time, i.e., from excitation to inhibition [42]. Neural recording studies have also found that the effects of direct current stimulation may attenuate during long stimulation blocks.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, event-related TDCS may selectively modulate only those circuits and task-related synapses that are contemporaneously active and undergoing concurrent plasticity [16,41]. As such, er-TDCS could prove beneficial when long experimental or rehabilitative protocols are required, as recent research suggests that long continuous bouts of TDCS may cause the resultant modulatory effects to diminish and even reverse over time, i.e., from excitation to inhibition [42]. Neural recording studies have also found that the effects of direct current stimulation may attenuate during long stimulation blocks.…”
Section: Resultsmentioning
confidence: 99%
“…Also, a higher tDCS intensity has been shown to reverse tDCS-induced neuroplastic effects in healthy people (63)(64)(65). For example, Hassanzahraee et al found that stimulation >1 mA for 26 min resulted in a reversal of anodal tDCS effects and was associated with a decrease in MEP amplitude and an increase in short-interval intracortical inhibition (63). However, these effects were also shown subsequently to be linked with the duration of the application (64), duration >26 min leading to a reversal of anodal stimulation.…”
Section: Lack Of Tdcs E Ectsmentioning
confidence: 99%
“…When using tDCS as a neuromodulatory technique for therapeutic purposes, it should be noted that the higher intensities or longer durations do not necessarily increase the expected effect of the used protocol [6,8]. It is important to know that the threshold for reaching the physiological limit for the reversal of the effect can be quite different in healthy population compared to patient populations which may be dependent on the synaptic history in the neurons in the stimulated area.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%